PERSPEKTIF PEMBELAJARAN BERINVESTASI PASAR MODAL DENGAN STIMULUS FREE OPENING ACCOUNT DI GALERI INVESTASI UNIVERSITAS SARJANAWIYATA TAMANSISWA - Cahya, Agus Dwi (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
This study aims to testing investment decision with free opening account stimulus from stock market learning and marketing mix perspectives in Galeri Investasi, Sarjanawiyata Tamansiswa University). The study was conducted by using simple random sampling towards 50 students who received free opening account facility from DIKTI 2015 research grant fund by Dr. Hj Sri Hermuningsih, SE.,MM. The employed analysis method was Partial Least Square (PLS), namely SEM, which is based on variance by using SmartPLS 3.0 software.The study shows: (1) Stock Market Learning does not significantly influence stock Investment Decision with significance of 0.967, (2) Product Knowledge does not significantly influence stock Investment Decision with significance of 0.113, (3) Opening Account Price significantly influences stock Investment Decision with significance of 0.034, (4) Place does not significantly influence stock Investment Decision with significance of 0.394, (5) Stock Market Learning, Product Knowledge, Opening Account Price, Place, and Promotion of Galeri Investasi BEI-UST altogether, significantly influence stock investment decision with significance of 0.006, (6) Free Opening Account Stimulus Moderation does not significantly influence stock market learning by investment decision of UST students with significance of 0.328. Keywords: Decision, Learning, Product, Price, Stimulus